2002
DOI: 10.1677/joe.0.1720247
|View full text |Cite
|
Sign up to set email alerts
|

Potential role of activin A in follicular development during the second half of pregnancy in the golden hamster: utero-placental source of activin A

Abstract: Numerous antral follicles develop during the second half of pregnancy in the golden hamster. However, mechanisms regulating follicular development during this period are unknown. Because inhibin and activin are related to follicular development, these hormones were studied to gain insight into any potential roles in follicular development. Plasma inhibin A and B suddenly increased from day 8 of pregnancy, reached peak levels on day 10 and gradually declined to term. Plasma activin A gradually increased from da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
12
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 30 publications
3
12
1
Order By: Relevance
“…Our immunohisochemical approach suggests that the inhibin/ activin subunits bA and bB localize in the syncytiotrophoblast of the placenta, indicating secretion of activin A, AB, or B from these cells. From these results, in the second half of pregnancy in the golden hamster, we postulate that placenta is a potent source of activin A, consistent with our previous report [10]. Activin was discovered to be a secretagogue factor of FSH [12,23,24].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our immunohisochemical approach suggests that the inhibin/ activin subunits bA and bB localize in the syncytiotrophoblast of the placenta, indicating secretion of activin A, AB, or B from these cells. From these results, in the second half of pregnancy in the golden hamster, we postulate that placenta is a potent source of activin A, consistent with our previous report [10]. Activin was discovered to be a secretagogue factor of FSH [12,23,24].…”
Section: Discussionsupporting
confidence: 90%
“…It is believed that in the golden hamster, the antral follicles that develop in the second half of pregnancy supply enough estrogens to maintain pregnancy, leading to parturition. We previously reported that during this period, large amounts of activin A are secreted from the placenta [10]. Our previous studies also suggest that this activin A is the factor that is involved in developing the antral follicles that emerge at the same time during the second half of pregnancy.…”
Section: Introductionmentioning
confidence: 77%
“…Both A and B subunits can also combine with the subunit and form inhibin-A ( A) and -B ( B) respectively. In the ovary, activin-A is the most studied type (Tisdall et al 1994, Yokota et al 1997, Zhao et al 2001, Thomas et al 2003 and plays an important role in ovarian follicle development (Ohshima et al 2002, Lovell et al 2003, but activin-B has also been described (Bristol & Woodruff 2004). The activities of activin are modulated by its binding protein follistatin, which was originally purified from mammalian follicular fluid as a FSH inhibitor (Phillips & de Kretser 1998).…”
Section: Introductionmentioning
confidence: 99%
“…and estradiol-17β is altered [2,3]. Maximal values of circulating inhibins, activin A, progesterone and estradiol-17β are noted during the second half of pregnancy, followed by a decrease at the end of pregnancy [2,3].…”
mentioning
confidence: 98%
“…Maximal values of circulating inhibins, activin A, progesterone and estradiol-17β are noted during the second half of pregnancy, followed by a decrease at the end of pregnancy [2,3]. In addition, a large number of antral follicles develop during the second half of pregnancy [4], whereas all large antral follicles degenerate at the end of pregnancy because of a lack of post partum ovulation [4,5], as seen in rats [6] and mice [7].…”
mentioning
confidence: 99%